2017
DOI: 10.2298/pac1702106d
|View full text |Cite
|
Sign up to set email alerts
|

Crucial effect of SiC particles on in situ synthesized mullite whisker reinforced Al2O3-SiC composite during microwave sintering

Abstract: Mullite whisker reinforced Al 2 O 3 -SiC composites were in situ synthesized by microwave sintering at 1500°C for 30 min. The influence of SiC particle size on heating process and properties of Al 2 O 3 -SiC composite were investigated. The XRD and SEM techniques were carried out to characterize the samples. The thermal shock resistance and flexural strength of the samples were examined through water quenching and three-point bending methods, respectively. It was found that the bridging of mullite whisker appe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…SiC phase was still detectable in the samples after crack-healing because SiC particles on the surface and cracks are only exposed to air and get oxidized into SiO 2 and the SiC particles within the surfaces are not getting oxidized. In previous studies, it was also observed that a SiO 2 phase forms in all four traditional sintering compositions, but only a small amount of SiO 2 forms in 15 and 20 wt.% of SiC composites synthesized by microwave sintering due to the shorter sintering time [19,20] Advances in Materials Science and Engineering crack-healing are shown in Figure 5. After crack-healing heat treatment at 1200°C for 1h in air, the surface of specimen became rough due to the oxidization of the particles.…”
Section: Phase Variation Aftermentioning
confidence: 85%
See 1 more Smart Citation
“…SiC phase was still detectable in the samples after crack-healing because SiC particles on the surface and cracks are only exposed to air and get oxidized into SiO 2 and the SiC particles within the surfaces are not getting oxidized. In previous studies, it was also observed that a SiO 2 phase forms in all four traditional sintering compositions, but only a small amount of SiO 2 forms in 15 and 20 wt.% of SiC composites synthesized by microwave sintering due to the shorter sintering time [19,20] Advances in Materials Science and Engineering crack-healing are shown in Figure 5. After crack-healing heat treatment at 1200°C for 1h in air, the surface of specimen became rough due to the oxidization of the particles.…”
Section: Phase Variation Aftermentioning
confidence: 85%
“…Microwave sintering is viewed as a prevailing method than conventional sintering processes because it can provide enhanced mechanical properties and better finer microstructure with minimum energy consumption [12,13]. Microwave sintering has been successfully used to synthesize Al 2 O 3 -based structural ceramics with constructive mechanical properties [14][15][16][17][18][19][20][21][22]. In order to produce crackhealing in Al 2 O 3 /SiC structural ceramic composites, the presence of SiC phase after sintering process was very much needed.…”
Section: Introductionmentioning
confidence: 99%
“…In the present investigation, the SiC/Al 2 O 3 composites reinforced by in situ mullite were prepared. In the previous research, the optimum sintering temperature, holding time, volume fraction of SiC particles, and volume fraction of Al 2 O 3 particles about the mullite reinforced SiC/Al 2 O 3 composites were 1500 °C, 30 min, 50%, and 50%, respectively [14]. erefore, the above sintering parameters were also used here.…”
Section: Introductionmentioning
confidence: 99%
“…Not only the morphology of the reinforcing phase but also the chemical compatibility and thermal expansion match of the reinforcing phase and matrix could influence the preparation process and final properties of SiC/ Al 2 O 3 composites. e recent research showed that particles and whiskers can greatly improve the strength and toughness of the ceramic matrix composites [13][14][15][16]. For whisker reinforced composites, the improvement is due to the changes of the microstructure, interface strengthening, and fracture mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of insufficient mechanical properties and oxidation resistance of a single phase ceramics, com-posite ceramics can be prepared by adding additives such as SiC, MoSi 2 , ZrN and BN to improve relevant properties [8][9][10][11][12]. Previous studies have proven that the addition of SiC can effectively improve mechanical properties and oxidation resistance of AlON ceramics [13,14].…”
Section: Introductionmentioning
confidence: 99%